On the Optimal Synthesis of a Finger Rehabilitation Slider-Crank-Based Device with a Prescribed Real Trajectory: Motion Specifications and Design Process - Araceli Zapatero-Gutiérrez; Eduardo Castillo-Castañeda; Med Amine Laribi (Applied Sciences, 2021)
This article discusses the mechanical redesign of a finger rehabilitation device based on a slider-crank mechanism. The redesign proposal is to obtain a smaller and more portable device that can recreate the motion trajectories of a finger. The real finger motion trajectories were recorded using a motion capture system. The article focused on the optimal synthesis of the rehabilitation device mechanism formulated as a classic trajectory generation problem. The proposed approach was combined with the recorded finger movements and solved using the genetic algorithm (GA) method. Optimization criteria and constraints were successively formulated and solved using a mono-objective function.